2010
DOI: 10.1007/s00068-010-0065-2
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis following major skeletal trauma: a systematic review

Abstract: There is currently insufficient research to be able to inform trauma surgeons as to the optimal method of thromboprophylaxis for patients following major skeletal trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…Some data suggest that pneumatic compression is as effective as heparin in reducing deep vein thrombosis (DVT) incidence [11][12][13]. Another systematic review suggested that low molecular weight heparin may be superior to unfractionated heparin, with no significant difference between unfractionated heparin versus mechanical compressions [14]. Between 1979 and 1999, despite all the advances, the incidence of DVT in hospitalized patients increased from 0.8% to 1.3% of admissions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Some data suggest that pneumatic compression is as effective as heparin in reducing deep vein thrombosis (DVT) incidence [11][12][13]. Another systematic review suggested that low molecular weight heparin may be superior to unfractionated heparin, with no significant difference between unfractionated heparin versus mechanical compressions [14]. Between 1979 and 1999, despite all the advances, the incidence of DVT in hospitalized patients increased from 0.8% to 1.3% of admissions [15].…”
Section: Introductionmentioning
confidence: 99%